2013
DOI: 10.1111/desc.12036
|View full text |Cite
|
Sign up to set email alerts
|

Statistical word learning at scale: the baby's view is better

Abstract: A key question in early word learning is how children cope with the uncertainty in natural naming events. One potential mechanism for uncertainty reduction is cross-situational word learning – tracking word/object co-occurrence statistics across naming events. But empirical and computational analyses of cross-situational learning have made strong assumptions about the nature of naming event ambiguity, assumptions that have been challenged by recent analyses of natural naming events. This paper shows that learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
129
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 29 publications
9
129
1
Order By: Relevance
“…However, this difference only emerged when children were grouped according to one aspect of their expressive language, phonology or vocabulary/grammar. Some researchers suggest that early language learning takes place during unstructured social interactions (e.g., Hoff, 2003) during which children must learn to selectively allocate their attention (Posner & Petersen, 1990; for a contrasting view, see Yurovsky, Smith, & Yu, 2013). Thus, children who respond to their communication partner's bids for joint attention are more likely to allocate their attention to relevant information that supports language learning.…”
Section: Discussionmentioning
confidence: 99%
“…However, this difference only emerged when children were grouped according to one aspect of their expressive language, phonology or vocabulary/grammar. Some researchers suggest that early language learning takes place during unstructured social interactions (e.g., Hoff, 2003) during which children must learn to selectively allocate their attention (Posner & Petersen, 1990; for a contrasting view, see Yurovsky, Smith, & Yu, 2013). Thus, children who respond to their communication partner's bids for joint attention are more likely to allocate their attention to relevant information that supports language learning.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we examined referential transparency (i.e., whether parents talk about observable referents), which is suggested to facilitate language learning (33)(34)(35). Notably, previous research examining why infants learn common nonnouns (e.g., "hi," "eat") later than common nouns found that visual copresence varied across word class (36).…”
mentioning
confidence: 99%
“…Using the HSP, Medina, Snedeker, Trueswell, and Gleitman (2011) found that approximately 90% of learning episodes were ambiguous (< 33% accuracy) and only 7% were relatively unambiguous (> 50% accuracy). In contrast, Yurovsky, Smith, and Yu (2013) found a higher proportion of clear naming events, with approximately 30% being unambiguous (> 90% accuracy). Consistent with this finding, Cartmill, Armstrong, Gleitman, Goldin-Meadow, Medina, and Trueswell (2013) showed that the proportion of unambiguous naming episodes varies across parent-child dyads, with some parents rarely providing highly informative contexts and others' doing so relatively more often.…”
Section: Introductionmentioning
confidence: 69%
“…Moreover, studies outside the domain of language acquisition have shown that the presence of social cues: (a) produce better spatial learning of 2 The differences in the estimates of referential uncertainty in these studies could be driven by the different sampling procedures used to select naming events for the HSP. Yurovsky, Smith, and Yu (2013) sampled utterances for which the parent labeled a co-present object, whereas Medina, Snedeker, Trueswell, et al (2011) randomly sampled any utterances containing concrete nouns. Regardless of these differences, the key point here is that variability in referential uncertainty across naming events exists and thus could alter the representations underlying cross-situational learning.…”
mentioning
confidence: 99%